Early childhood caries prevalence and associated risk factors among Saudi preschool children in Riyadh - Lujane K. AlMarshad; Amjad H. Wyne; Asma M. AlJobair (Saudi Dental Journal)
Aim: To determine the prevalence of early childhood caries (ECC) and investigate the effect of associated risk factors on ECC prevalence in preschool children in Riyadh, Saudi Arabia. Methods: This cross-sectional study included Saudi preschoolers aged 36–71 months. Parents/guardians completed a structured, self-administered questionnaire assessing sociodemographics; medical, dental, and dietary history; and oral hygiene practices. Children were orally examined for dental caries, oral hygiene, and plaque deposition. Results: A total of 383 children were examined. ECC prevalence was 72.6%, with a mean decayed, missing, and filled teeth (dmft) score of 4.13 (±3.99) and a mean decayed, missing, and filled surfaces (dmfs) score of 7.0 (±9.1). Children from schools in northern Riyadh and those of fathers in professional jobs were less likely to have ECC [(OR: 0.203; 95% CI: 0.082–0.503)] and [(OR: 0.472; 95% CI: 0.256–0.871)], respectively. Children with a nocturnal feeding history and poor oral hygiene were more likely to have ECC [(OR: 2.281; 95% CI: 1.143–4.553)] and [(OR: 5.523; 95% CI: 2.269–13.441)], respectively. Conclusions: The prevalence of ECC in preschool children in Riyadh is high and affected by parental socioeconomic factors, infant feeding practices, and children’s oral hygiene status.